ANALISIS DAMPAK GAME ONLINE FREE FIRE TERHADAP MOTIVASI BELAJAR DI RUMAH BAGI SISWA SEKOLAH DASAR - hakim, numan; Aah Ahmad Syahid; Aeni, Ani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the impact of playing the online game Free Fire on elementary school students’ learning motivation at home. The background of this research stems from the increasing intensity of online gaming among children, which is suspected to reduce their interest and motivation to study. A qualitative approach with a phenomenological method was employed in this research. The subjects consisted of 13 elementary school students who played Free Fire for more than 2 hours a day. Data were collected through in-depth interviews and analyzed using descriptive qualitative techniques. The findings revealed that playing Free Fire affects various aspects, such as physical and mental health (eye strain, fatigue, irritability), decreased interest in studying, memory disturbances, and reduced independence and responsibility in learning. However, some students were able to manage their playing time and still showed good motivation to learn. The study concludes that Free Fire has a negative impact on students’ learning motivation, especially when played excessively without proper supervision.